2019
DOI: 10.52716/jprs.v9i3.314
|View full text |Cite
|
Sign up to set email alerts
|

Structural geology and petrophysics analysis to Injection wells of Mishrif Formation in Shuaiba Dome – Zubair Oil Field

Abstract: Mishrif formation is the one of the most important reservoir in Southern – Iraq   and the injection water important to support the reservoir pressure. The current study combined the interpretations of PLT, structural geology and petro-physics to understand the distribution of the injection rate for nine injection wells to the  Mishrif Formation in Shuaiba Dome (or culmination) - Zubair Oil Field. PLT analysis calculated injection rate for Mishrif Formation, structural analysis included geometric and genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Integration between geometric and genetic analysis results referred to that the study area may be controlled by tectonic activities. These results confirmed that the study area formed by same geological conditions of surrounding oilfields [22]- [25], [27], but with less intensity. The tectonic history of the study area passed through geological periods; Cretaceous, Paleogene, and Neogene Periods, and these have significant events, as shown in (Table 3).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Integration between geometric and genetic analysis results referred to that the study area may be controlled by tectonic activities. These results confirmed that the study area formed by same geological conditions of surrounding oilfields [22]- [25], [27], but with less intensity. The tectonic history of the study area passed through geological periods; Cretaceous, Paleogene, and Neogene Periods, and these have significant events, as shown in (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…There is no interpretation for gravity and magnetic geophysical data of the study area, but depending on the results of adjacent Oilfields and structures within the Zubair subzone (like Nahr Umr and Zubair Oilfields) the salt structures of Hormuz salt and basement faults has been indicated [11], [13], [14]. These geophysical results are linked with the oilfields' structural pictures and folding mechanisms (bending and buckle) [23]- [25]. Therefore, the bending mechanism could be attributed to the influence of salt structure-activity of Hormuz salt and/or reactivated basement faults as vertical force, while buckling mechanism to the collision between Arabian Plate and Eurasian Plate as a parallel force.…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation